On the Impact of Innovations on the Social Structure - Dmitriev, Sergey; Kalinicheva, Valentina; Shadoba, Elena; Nikonets, Olesya; Pogonysheva, Dina; Shvarova, Elena (International Journal of Economics and Financial Issues, 2016)
The paper investigates the problem, which does not attract much attention of economics and sociology researchers, concerning the impact of revolutionary technological and other innovations on the transformation of the social structure of modern states. The innovations, which are considered by most researchers as a driver for economic growth, cause significant changes. Some of these changes are negative. One of these negative consequences of innovative development is the middle class reduction in the social structure. The USA statistics over the last 50 years are a reliable source of information for this statement formulation. At the same time, not only developed countries but also developing ones face this trend. As the example, the paper presents the experience of such country as Ghana. Also the paper discusses the problem concerning the growth of unemployment as a result of the implementation of technological innovations into production. As shown below, contrary to expectations the fourth industrial revolution will create fewer jobs than they were in the past and will also have an impact on the social structure. Keywords: innovation, economic growth, inequality, middle class, social structure, the fourth industrial revolution JEL Classifications: LOO, O1, O40